Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan (Studi Pada Mahasiswa/i Program Strata-1 FISIP UNDIP) - Raka Rizky Saputra; Sudharto P Hadi (Jurnal Ilmu Administrasi Bisnis, 2017)
The low of customer satisfaction gives an impact, both for the consumers and producers. For the consumer, the low of customer satisfaction led to customers being disappointed and select the products or services offered by the competitors. As for the producers, the low of customer satisfaction affects the volume of sales. The number of ISP Mobile Telkomsel Flash customers, especially in the city of Semarang seen from data on the number of customers has fluctuated.The purpose of this study was to determine the effect of service quality and price to customer satisfaction Telkomsel Flash. This type of research is explanatory research. Samples were set at 97 respondents who are students of undergraduate programme FISIP UNDIP using snowball sampling technique. The techniques of data analysis using validity test, reliability test, crosstab analysis, correlation coefficient, multiple correlation coefficient, determination coefficient, simple linear regression analysis, multiple linear regression analysis, significance test (t-test), and a simultaneous test (F-test) were processed using SPSS programme 20th version.Based on the analysis, the quality of service and price has an influence on customer satisfaction, either partially or simultaneously. The variable of price provide a greater influence on customer satisfaction amounted to 65,2% of the variable quality of service amounted to 41,3%.Suggestions for PT. Telkomsel Regional Central Java and Yogyakarta as a service provider Telkomsel Flash is to improve the quality of services provided, particularly in terms of the distribution of quotas are balanced, both national quotas and quota based zone region when doing activation and policies to raise the price, expected according to the purchasing power of customers and services rendered so as to provide more value for customers.